Antifibrotic and anti-inflammatory effects of the selective nonsteroidal MR antagonist finerenone in preclinical pulmonary fibrosis. (14th October 2021) - Delbeck, M; Joseph, A; Pitt, B; Kolkhof, P
Abstract: Background: Patients with idiopathic pulmonary fibrosis (IPF) are at increased risk of developing coronary artery disease (CAD) with a median survival of 3.5 years after diagnosis. Cardiac and pulmonary fibrosis share several common signaling pathways including TGF-β-related collagen synthesis. Pirfenidone and nintedanib were the first approved medical antifibrotic IPF therapies that inhibit TGF-β–related collagen synthesis or multiple receptor tyrosine kinases, respectively. However, the role of mineralocorticoid receptor blockade in IPF is less well understood. Purpose: To test the hypothesis that the selective nonsteroidal MR antagonist finerenone has antifibrotic and anti-inflammatory activity in preclinical IPF. Methods: Anti-fibrotic/anti-inflammatory efficacy was investigated in two different mouse models of pulmonary fibrosis. Lung fibrosis was induced by either intranasal application of bleomycin (1 mg/kg) or intratracheal application of silica particles (2.5 mg/mouse). Bleomycin-treated C57BL6 mice (8 weeks old male, n=10–15/group) were administered once daily orally from day 7 to 21 with vehicle (ethanol/solutol/water), finerenone (10 mg/kg) or nintedanib (60 mg/kg) in vehicle. Silica-treated C57BL6 mice (8 weeks old male, n=10–12/group) were administered once daily orally from day 7 to 30 with vehicle (ethanol/solutol/water), finerenone (1 or 10 mg/kg) or nintedanib (100 mg/kg) in vehicle, or with pirfenidone (800mg/kg/d) via chow. At day 21 and 30 respectively, histological examination of pulmonary fibrosis using immunohistochemistry (COL1A1 positive tissue area in %) and Ashcroft score as well as profibrotic and pro-inflammatory cytokine and COL1A1 protein level (ELISA) analysis in lung homogenate were performed. Results: Bleomycin caused a significant increase in lung COL1A1 positive tissue area and Ashcroft Score and silica-induced lung pathology additionally showed elevated IL-1beta, IL-6, IL-10, IL-12p70, TNFalpha and COL1A1 protein levels in lung tissue. Therapeutic treatment with finerenone as well as nintedanib from day 7–21 significantly reduced the percentage of lung COL1A1 positive tissue and Ashcroft score in the bleomycin mice model without a significant difference between treatment groups. Furthermore, finerenone significantly reduced lung COL1A1 as well as IL-1beta, IL-6, IL-10, IL-12p70 and TNFalpha protein levels in lung homogenate after a therapeutic treatment from day 7–30 in the silica mice model, whereas nintedanib showed only a reduction in lung COL1A1 and IL-10 levels and treatment with pirfenidone was without significant effects. There was a significant difference in the reduction of lung IL-12p70 and TNFalpha protein levels between finerenone 10 mg/kg and nintedanib as well as pirfenidone treatment. Conclusion: Nonsteroidal MR antagonism by finerenone showed anti-fibrotic/anti-inflammatory efficacy in two animal models of pulmonary fibrosis and may impact the progressive course of fibrotic diseases. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): BAYER AG